When scientists meet the public: an investigation into citizen cyberscience - Darch, P (2011)
Citizen Cyberscience Projects (CCPs) are projects mediated through the Internet, in which teams of scientists recruit members of the public (volunteers) to assist in scientific research, typically through the processing of large quantities of data. This thesis presents qualitative ethnographic case studies of the communities that have formed around two such projects, climateprediction.net and Galaxy Zoo. By considering these social actors in the broader contexts in which they are situated (historical, institutional, social, scientific), I discuss the co-shaping of the interests of these actors, the nature of the relationships amongst these actors, and the infrastructure of the projects and the purposes and nature of the scientific work performed. The thesis focusses on two relationships in particular. The first is that between scientists and volunteers, finding that, although scientists in both projects are concerned with treating volunteers with respect, there are nevertheless considerable differences between the projects. These are related to a number of interconnecting factors, including the particular contexts in which each project is embedded, the nature of the scientific work that volunteers are asked to undertake, the possibilities and challenges for the future development of the projects as perceived by the scientists, and the tools at the disposal of the respective teams of scientists for mediating relationships with volunteers. The second is amongst the volunteers themselves. This thesis argues that volunteers are heterogeneous, from disparate backgrounds, and that they sustain their involvement in CCPs for very different purposes. In particular, they seek to pursue these through the way they negotiate and construct their relationships with other volunteers, drawing on particular features of the project to do so. This thesis contributes to two fields. The first is to Citizen Cyberscience itself, with a view to improving the running of such projects. Some social studies have already been conducted of CCPs to this end, and this thesis both extends the analysis of some of these pre-existing studies and also problematizes aspects of CCPs that these studies had not considered. I discuss the significance of my findings for those involved in setting up and running a CCP, and present some recommendations for practice. The second field is Science and Technology Studies, in particular studies of public engagement with scientific and technological decision- and knowledge-making processes. The modes of engagement found in CCPs differ in key ways from those that have already been documented in the existing literature (in particular, different power relationships) and thus offer new ways of understanding how the public might be engaged successfully in such processes.